Math 1211 Written Assignment Unit 5
docx
keyboard_arrow_up
School
University of the People *
*We aren’t endorsed by this school
Course
1211
Subject
Mathematics
Date
Nov 24, 2024
Type
docx
Pages
3
Uploaded by AngelRoseBenedict
1.
Find the derivative for the function Given:
f(x) = 2
ex
− 8
x
d/dx (2
ex
) = 2 ⋅ d/dx e
x = 2e
x
d/dx 8
x
= 8
x
⋅ ln(8)
Therefore, the derivative of the function f(x)=2
ex
−8
x
is:
= 2
ex
− 8
x
⋅
ln(8)
2.
Find the derivative for the function
Differentiating z
5
with respect to z using the power rule (d/dz z
n = n ⋅ z
n−1
):
d/dz (z
5
) = 5z
5
– 1 = 5z
4
u = d/dz ′
e
z
= e
z (since the derivative of e
z
is e
z
)
v = d/dz ln(z) = 1/z (using the derivative of ln(z))
′
Applying the product rule:
d/dz (e
z
l n(z)) = e
z
⋅
ln(z) + e
z ⋅ 1/z
Therefore, the derivative of the function 𝑓
’(
𝑧
) = 5
𝑧
4 − 𝑒
𝑧
/z
− 𝑒
𝑧
ln (
𝑧)
3.
Find the tangent line to at f (0) = 7
′
0
ln(7) + 4e
0
f (0) = ln(7) + 4
′
f(0) = 7
0
+ 4e
0
f(0) = 1 + 4 = 5
At x = 0 y=5.
y−5 = (ln(7)+4) (x−0)
y = 5 + (ln(7) + 4)x
4.
Determine if is increasing or decreasing at the following points.
(a) z=1
f (z) = d/dz ′
(z − 6) = 1
g (z) = d/dz ln(z) = 1/z
′
Now applying the product rule:
G (z) = f (z)g(z) + f(z)g (z)
′
′
′
G (z) = 1 ′
⋅ ln(z) + (z−6) ⋅ 1/z
G (z) = ln(z) + z ′
– 6 / z
To determine the behavior of G(z) at z=1, let's evaluate G (1):
′
G (1) = ln(1) + 1
′
− 6 / 1= 0 − 5= −5
Since G (1) = −5 < 0, the function G(z) = (z−6)ln(z) is decreasing at z=1. ′
(b) z=5
G (5) = ln(5) + 5 – 6 / 5
′
G (5) = ln(5) ′
– 1/5
Since ln(5) is positive and 1/5 is positive as well, G (5) = ln(5) ′
− 1/5 is positive overall.
Therefore, as G (5)>0, the function G(z) = (z−6)ln(z) is increasing at z=5.
′
(c) z=20
The natural logarithm of 20 is positive and 7/10 is positive as well, hence G′(20) = ln(20) + 7/10 is positive
overall.
Therefore, as G′(20)>0, the function G(z) = (z−6)ln(z) is increasing at z=20.
5.
Find the derivative for the function f(x) = (x + 1)
x
d/dx (ln(y)) = d/dx (x ⋅
ln(x+1))
1/y ⋅
dy/dx = ln(x+1) + x
⋅
1 / x + 1
1/(x+1)
x
⋅ dy/dx = ln(x + 1) + x / x+1x
= (x + 1)
x
⋅ (ln(x + 1) + x / x+1)
6.
Find the derivative for the function
y = x
x+1
, so is the derivative of f(x):
1/x
x+1 ⋅ dy/dx = ln(x) + x+1 / x
Multiply both sides by x
x+1 to solve for dy/dx, the derivative of f(x):
= x
x+1 ⋅ (ln(x) + x+1 / x)
7.
Find the derivative for the function f(x) = (x
1/2
)
x
f (x) = x
′
x
⋅ (1/2 ⋅ ln(x) + 1/2)
= f (x) = ½ (ln(x) + 1)(
′
√x)
x 8.
Find for
dy/dx = 3
x
(
3
x
4
+
1
)
2
¿¿
9.
Find for dy
dx
= 3x
3x ⋅ (3 ⋅ ln(3x) + 3)
dy
dx
= 9x
3x ⋅
(ln(3x) + 1)
Your preview ends here
Eager to read complete document? Join bartleby learn and gain access to the full version
- Access to all documents
- Unlimited textbook solutions
- 24/7 expert homework help